Self-Efficacy and Depression in Boxers: A Mediation Model - Chen, Xin; Qiu, Nan; Chen, Chao; Wang, Dexin; Zhang, Guodong; Zhai, Liang (Frontiers in Psychiatry, 2020)
Background: Depression has become one of the most common problems faced by athletes in many mental health problems, its production and development mechanisms and influencing factors have received wide attention from researchers, whereas boxer’s depression has received limited attention. This study explored the relationship between boxer’s self-efficacy and depression, as well as the effect of self-control as a mediating factor. Methods: This study used The Athlete Self-Efficacy Scale, The Self-Control Scale, and The Center for Epidemiologic Studies Depression Scale. Using a large number of random selected samples method, N=231 boxers (age: M =20.28, SD =2.60, ages around 18 to 32; amount of number of years of exercise: M = 6.07 years, SD = 2.90, years around 1 to 15; 144 male) of Chinese national athletes participated the study. Results: Self-efficacy and self-control were negatively correlated with depression; self-efficacy was positive correlated with self-control. In addition, self-control played a partial mediation role between self-efficacy and depression among boxers． Conclusion: That goes unstated, important ways to improve and prevent the depression of Chinese boxers may be enhance the level of self-efficacy and self-control.